SOCIAL CONNECTEDNESS AND LONELINESS OF ELDERLY - Failusuf, Shafa Izdihara Minfadlika; Kusumaningrum, Fitri Ayu (JURNAL TALENTA PSIKOLOGI, 2022)
This study aims to determine the relationship between social connectedness and loneliness of elderly in Bekasi. The hypothesis in this study is that there is a negative relationship between social connectedness and loneliness of elderly in Bekasi. This study uses a social connectedness scale (8 items) adapted and refers to aspects of (Lee & Robbins, 1995) and loneliness which is adapted from (Neto, 2014) and refers to aspects of (Russell, 1980). The subjects of this study amounted to 116 elderly people in Bekasi aged at least 60 years who were male and female and active in communicating. The results of the data show the correlation coefficient r = - 0.580 with a significance of p = 0.000 so it can be said that the hypothesis is accepted.